12 Dynamic Wave Arc with SBRT dedicated system VERO: Implementation and quality control. (December 2018) - Mazurier, J.; Marre, D.; Mathy, N.; Zarate, D.; Camilleri, J.; Gallocher, O.; Jimenez, G.; Pinel, B.; Chevelle, C.; Franck, D; Latorzeff, I.
Abstract : Introduction: With SRS/ SBRT, non coplanar beams with fixed table positions are widely used. Since 2017, the dedicated accelerator SBRT VERO (Brainlab, Mitsubishi) has a new treatment approach allowing simultaneous gantry/ring rotations according to predefined trajectories: Dynamic Wave Arc (DWA), realizing in 1 arc a dynamic non coplanar VMAT treatment. This work presents the implementation and the quality control of the DWA. Methods: The Vero system is equipped with a gimballed irradiation head with MLC in order to follow tumor movements (Dynamic Tacking DT), on board on a O' ring. TPS Raystation (Raysearch) has recently developed for the VERO system, a specific optimization module for the DWA technique. Dosimetric data for the VERO beam modelling in the TPS and its validation, were measured with Edge diode (SunNuclear) and 0.125 cc ionization chamber (PTW) with the 3DS circular water tank (SNC) mounted on the O'ring (Jack screwed on the ring). The agreement measurements/calculations was evaluated with ScanDoseMatch software (qxrayconsulting.com). MLC characteristics (MLC position, effet Tongue and Groove, Leaf tip, Transmission..) were defined with MLC test fields, EBT3 films and analysis film software Doselab Pro. The validation of the beam modeling was performed according the ESTRO 2004 protocol. Clinical tests for IMRT, VMAT and DWA irradiations were performed with several detectors and phantoms: EBT3 films calibrated according to a well defined procedure allowing a dosimetric accuracy of 3%, the CIRS062 phantom, the 3D matrix Archeck (SunNuclear), and the StereoPhan system (SunNuclear) combined with the new diodes matrix SRSMapcheck (SunNuclear). This new matrix is composed of 1013 diodes in a 7.7x7.7 cm 2 field and allows measurements with non coplanar beams (angular diode corrections). The agreement between calculated and measured dose distributions was calculated with gamma index method and different criteria according to the measurement system used. Results: The beam modeling in Raysearch shows that 95% of the tests have γ < 1 for 2%1 mm. The MLC characteristics MLC position, Transmission, Leaf Tip et Tongue and Groove allowing an agreement for the tested MLC are respectively 0.008 cm, 0.2%, 0.3 cm and 0.03 cm. The clinical results give an agreement between calculations and measurements with γ < 1 for (2%2 mm) with Archeck, (3%1 mm) for EBT3 films et (2%1 mm) for SRSMapcheck. Conclusion: DWA is a reliable technology for a fast treatment with 1 modulated arc according non coplanar trajectories. The next step would be to associate DWA to the Dynamic Traking(DT).